The Signaling Hypothesis Revisited: Evidence from Foreign IPOs - Francis, Bill B.; Hasan, Iftekhar; Lothian, James R.; Sun, Xian (Journal of Financial and Quantitative Analysis, 2010)
Abstract While the signaling hypothesis has played a prominent role as the economic rationale associated with the initial public offering (IPO) underpricing puzzle (Welch (1989)), the empirical evidence on it has been mixed at best (Jegadeesh, Weinstein, and Welch (1993), Michaely and Shaw (1994)). This paper revisits the issue from the vantage point of close to two decades of additional experience by examining a sample of foreign IPOs—firms from both financially integrated and segmented markets—in U.S. markets. The evidence indicates that signaling does matter in determining IPO underpricing, especially for firms domiciled in countries with segmented markets, which as a result face higher information asymmetry and lack access to external capital markets. We find a significant positive and robust relationship between the degree of IPO underpricing and segmented-market firms’ seasoned equity offering (SEO) activities. For firms from integrated markets, in contrast, the analyst-coverage purchase hypothesis appears to matter more in explaining IPO underpricing, and the aftermarket price appreciation explains these firms’ SEO activities. The evidence, therefore, clearly supports the notion that some firms are willing to leave money on the table voluntarily to get a more favorable price at seasoned offerings when they are substantially wealth constrained, a prediction embedded in the signaling hypothesis.